Martin Luther's Lectures on Romans (1515-1516): Their Rediscovery and Legacy - Wiersma, Hans H. (Word & world, 2019)
It was his new reading of Romans that led Martin Luther to his evangelical breakthrough. But scholars have long argued about the dating and nature of that breakthrough. With the rediscovery of Luther’s early lectures on Romans, we received a window into his breakthrough and his new understanding of God’s justification of the Christian person.